The Rose playhouse in context - Mao, Y (2016)
This thesis conducts the first book-length study on the operation of the Rose playhouse as a key theatrical presence whose operational history spanned over a transitional period for early modern English theatre. Inspired by the current increasing awareness of the playing company as an organising unit in additional to the author-based perspectives for studying early modern English drama, this project undertakes the task of examining the Rose playhouse as a unit for theatrical production and a nexus where various strands of the material, cultural-geographical, political, financial, as well as literary forces converged and interacted with each other.